Early Increase of Circulating Transitional B Cells and Autoantibodies to Joint‐Related Proteins in Patients With Metastatic Melanoma Developing Checkpoint Inhibitor–Induced Inflammatory Arthritis. Issue 5 (14th March 2023) - Gatto, Mariele; Bjursten, Sara; Jonsson, Charlotte A.; Agelii, Monica Leu; Jonell, Caroline; McGrath, Sarah; Lönnblom, Erik; Sareila, Outi; Holmdahl, Rikard; Rudin, Anna; Levin, Max; Gjertsson, Inger
Abstract : Objective: To investigate potential associations between B cell–related immunologic changes and development of inflammatory arthritis (IA) after treatment with immune checkpoint inhibitors (ICIs). Methods: Patients who developed ICI‐induced IA (ICI‐IA) and patients who did not develop immune‐related adverse events (non‐IRAE) after receiving ICIs to treat metastatic melanoma were consecutively recruited. Blood samples were collected at the time of ICI‐IA occurrence and at different time points during treatment. Peripheral blood B cell subsets during ICI treatment were analyzed by flow cytometry. Rheumatoid factor, anti–citrullinated protein antibodies, and antibodies against joint‐related proteins were measured. Results: Proportions of CD19+ B cells were higher in patients with ICI‐IA (n = 7) compared to patients with non‐IRAE (n = 15) (median 11.7% [interquartile range (IQR) 9.7–16.2%] versus 8.1% [IQR 5.7–11.0%]; P = 0.03). The proportion and absolute numbers of transitional CD19+CD10+CD24 high CD38 high B cells were increased in patients with ICI‐IA compared to non‐IRAE patients (median 8.1% [IQR 4.9–12.1%] versus 3.6% [IQR 1.9–4.9%]; median 10.7 cells/μl [IQR 8.9–19.6] versus 4.4 cells/μl [IQR 2.3–6.6]; P < 0.01 for both). In addition, higher levels of transitional B cells were associated with development of ICI‐IA (odds ratio 2.25 [95% confidence interval 1.03–4.9], P = 0.04). Transitional B cells increased before the onset of overt ICI‐IA and decreased between the active and quiescent stages of ICI‐IA ( P = 0.02). Autoantibodies to type II collagen epitopes were detected in up to 43% of ICI‐IA patients compared to none of the non‐IRAE patients ( P = 0.02). Conclusion: Development of ICI‐IA is accompanied by an increase in transitional B cells and by production of autoantibodies to joint‐related proteins. Monitoring of B cell–driven abnormalities upon ICI treatment may help earlier recognition of ICI‐IA. Abstract :